2014
DOI: 10.1080/01904167.2014.920373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Humic Substance Levels on Growth and Nutrient Concentration of Corn under Calcareous Conditions

Abstract: 2 This study investigated the effect of high humic substance (HS) levels (0, 500, 1000, and 2000 mg HS kg −1 ) on growth and nutrient concentrations of corn grown on calcareous soils. For these, soil samples were collected from the six different provinces of Turkey. According to the average values, HS levels had no significant effect alone on dry weight, nitrogen (N), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), copper (Cu), and manganese (Mn) concentrations. Soil differences significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Kamari et al [42] also reported the immobilization of heavy metals in soil with manure applications in some studies and depended on the effectiveness of stabilization to the nature of contaminants, physical and chemical characteristics of the amendment and also the type of soil. On the other hand formation of organa-metal compounds may increase the solubility of heavy metal and availability in plants [37]. Parallel to the findings of us, Arroyo et al [43] also pointed increased concentrations of Cu in plants grown on the poultry manure amended soils.…”
Section: Effects Of Chicken Manure On Some Heavy Metal Amountssupporting
confidence: 70%
See 1 more Smart Citation
“…Kamari et al [42] also reported the immobilization of heavy metals in soil with manure applications in some studies and depended on the effectiveness of stabilization to the nature of contaminants, physical and chemical characteristics of the amendment and also the type of soil. On the other hand formation of organa-metal compounds may increase the solubility of heavy metal and availability in plants [37]. Parallel to the findings of us, Arroyo et al [43] also pointed increased concentrations of Cu in plants grown on the poultry manure amended soils.…”
Section: Effects Of Chicken Manure On Some Heavy Metal Amountssupporting
confidence: 70%
“…It has been stated that humic acids are effective on plant growth and development, and when applied in small quantities, it positively affects the development of plants. However, when applied in large quantities, ineffective or even quite negative effects on development were also reported [37].…”
Section: Effects Of Chicken Manure On Dry Weight Amountsmentioning
confidence: 99%
“…Similarly, minimum aphid population was also noticed in the same treatment (Figure 1). Leventoglu and Erdal, stated that higher levels of organic matters can bind soil nutrients as unavailable forms, thus plants cannot grow better in the terms of yield and quality traits [55]. Due to large particulate surface areas, vermi-composts provide many micro sites for microbial activity and for the strong retention of nutrients [56].…”
Section: Discussionmentioning
confidence: 99%
“…Of the humic substances, coal‐derived potassium (K + ) and Na + humate are produced commercially for agricultural and industrial use, but surprisingly there is very little in the scientific literature on the effects of these types of commercial humates on plant growth or yield. The limited studies to date have reported mixed results (Sharif et al ., ; Van Tonder, ; Tahir et al ., ; Turan et al ., ; Leventoglu & Erdal, ). Our preliminary experiments investigating ameliorative effects of Na + humate on salinity‐stressed barley, bread wheat and durum wheat showed that at all salinities, Na + humate (2–4 g kg −1 potting mix) reduced plant growth at heading by 10–20% depending on cereal species and degree of salinity stress (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 98%